Case Study : Wadie Bakery & Cake / Abdul Azim Mohamed Nawi - Mohamed Nawi, Abdul Azim (2021)
The original purpose of this case study conducted because to expose students to real business through this case study. through this case study, students can identify the individual situation such as person, business and entrepreneurial competencies in more details. For this case study, I have done interview and research about company that I have selected and identified the company background also the entrepreneur in details. The name of company that I have choose is Wadie Bakery & Cake and in accordance with the name of company, the founder of this company is Mohd Yuswadi Mohd Zawizah. This case study will also tell us about its success and fluctuations in doing business over the years. At the end of the case study, we managed to gain a lot of new knowledge about business in the real world. In addition, the potential of our country is also determined by the entrepreneurs we have today. To share to the public, Mohd Yuswadi is very hard worker, he never gave up on his business, no wonder today he enjoys various successes. In conclusion, this project is good for students as they learn about business in their lives. Mohd Yuswadi's success can motivate us all to start a business. It was a good experience.